A trail of storms imprinted in Triassic rocks on the touristic path: an example from Grodziec (Dąbrowa Basin, southern Poland) - Gawęda, Aleksandra; Vierek, Aleksandra (Geotourism/Geoturystyka, 2018)
The Upper Silesia – Dąbrowa Basin is one of the highest industrially transformed regions in Europe. However, places of geotouristic value are still preserved and should be protected. One of them is the abandoned “Kamionka” quarry and nearby St. Dorota hill, known as “local Olympus” with historical monuments, located in the Grodziec district of Będzin. The profile of Triassic limestones, dolomitized limestones and marly dolomites belong to so called Gogolin Beds and represent the sedimentation typical of sea transgression with numerous changes in water energy, up to stormy sedimentation, imprinted in rock textures and sedimentary structures. Both proximal and distal tempestites are found here. Local bioturbations are indicative for breaks in storm activity and low-energy sedimentation. In general, the carbonate sediments of Grodziec district were formed in shallow basin, on the carbonate ramp, influenced by storms and/or bottom currents. The link between the history of that area, geomorphology and geological features makes that area of special importance for geotourism.